Reallocation of cutaneous and global blood circulation during sauna bathing through a closed-loop model. (June 2022) - Li, Zhongyou; Jiang, Wentao; Fan, Haidong; Yan, Fei; Dong, Ruiqi; Bai, Taoping; Xu, Kairen
Highlights: A systematic description of the relationship between sauna bathing and global circulation, providing a promising strategy for explaining sauna bathing's role in the treatment of various diseases. Increased cutaneous perfusion is compensated by a reduction in visceral perfusion, which may contribute to angiogenesis to upregulate visceral function. Sauna bathing improves pulmonary circulation, which may be one of the mechanisms for its efficacy in lung diseases. Sauna bathing, however, increases retrograde flow in aortas, potentially influencing the local hemodynamic environment. This may lead to undesirable outcomes and should be taken into consideration in clinical practice. Abstract: Objective: Sauna bathing (SB) is an important strategy in cardiovascular protection, but there is no mathematical explanation for the reallocation of blood circulation during heat-induced superficial vasodilation. We sought to reveal such reallocation via a simulated hemodynamic model. Methods: A closed-loop cardiovascular model with a series of electrical parameters was constructed. The body surface was divided into seven blocks and each block was modeled by a lumped resistance. These resistances were adjusted to increase skin blood flow (SBF), with the aim of reflecting heat-induced vasodilation during SB. Finally, the blood pressure was compared before and after SB, and the blood flow inside the aorta and visceral arteries were also analyzed. Results: With increasing SBF in this model, the systolic, diastolic, and mean blood pressure in the arterial trunk decreased by 13–29, 18–36, and 19–37 mmHg, respectively. Despite the increase in the peak and mean blood flow in the arterial trunk, the diastolic blood flow reversal in the thoracic and abdominal aortas increased significantly. Nevertheless, the blood supply to the heart, liver, stomach, spleen, kidney, and intestine decreased by at least 25%. Moreover, the pulmonary blood flow increased significantly. Conclusion: Simulated heat-induced cutaneous vasodilation in this model lowers blood pressure, induces visceral ischemia, and promotes pulmonary circulation, suggesting that the present closed-loop model may be able to describe the effect of sauna bathing on blood circulation. However, the increase of retrograde flow in the aortas found in this model deserves further examination.